Effect of Sungkai Leaf Extract (Peronema canescens J.) on Colony Diameter and Percentage of Growth of Inhibition Fusarium oxysporum - Marisa Marisa; Moralita Chatri; Linda Advinda; Mades Fifendy (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
The purpose of this study was to determine the effect of the concentration of leaf extract P. canescens on colony diameter and the percentage of inhibition of growth of F. oxysporum. This research was conducted from November 2021 to December 2021, at the Integrated Research Laboratory of the Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This study was an experimental study consisting of 5 treatments and 3 replications with leaf extract at P. canescens concentrations of 0%, 10%, 20%, 30%, 40%. The data obtained were analyzed by means of variance (ANOVA) with Duncan's New Multiple Range Test (DNMRT) further test. The results showed that the leaf extract of P. canescens . Effect on the diameter of the fungal colonies of F. oxysporum. The concentration of leaf extract affected the percentage of growth of inhibition F.oxysporum. The lowest percentage of inhibition was at a concentration of 10% and the highest at a concentration of 40%.